AN ANALYSIS OF READING EXERCISES QUESTION INSERTED IN ENGLISH BOOK ORIENTED TO HOTS FOR THE TENTH GRADE STUDENTS OF SMKN 1 PENUKAL UTARA - Doraimon; Masagus Firdaus; Hanni Yukamana (Universitas PGRI Palembang, 2025)
English, as the lingua franca of our interconnected world, holds immense significance for contemporary students. Its status as a global language transcends borders, enabling communication across diverse cultures, industries, and regions. Proficiency in English is not merely a skill but a gateway to numerous opportunities, such as accessing international academic resources, participating in global job markets, and fostering cross-cultural understanding. This research underscores the critical role of English in modern education, highlighting its function in facilitating global collaboration and access to critical educational resources. Most scholarly literature and leading educational materials are in English, making proficiency in the language essential for keeping up with developments across various fields.This study employed a qualitative research design to explore the role of the